Sustainable Recycling of Vehicle Lubricant and Engine Oils for Environmental Protection - J.M. Rasheed, Hardy; Ismael, Karzan; J. Abdulla , Rebaz (International Journal of Sustainable Development Goals, 2025)
The rapid expansion of the global automotive industry has led to increased consumption of vehicle lubricant and engine oils, generating significant quantities of used lubricant oils (ULOs) annually. In many developing countries, improper disposal practice, such as dumping used oils into the sewage system pose severe environmental and public health threats, including water pollution and carcinogenic risks. This study explores a sustainable approach to managing and recycling ULOs within a circular economy framework. It highlights environmentally responsible technologies that enable the transformation of waste oils into valuable products such as re-refined lubricant oils, diesel-like fuels, light gases, and asphalt-like residues. By diverting hazardous waste from landfills and waterways, this recycling process not only reduces ecological damage but also supports resource efficiency and energy recovery. With the advancement of catalytic, thermal, and solvent-based methods, and support from environmental policies, nations can turn hazardous waste into economic opportunity. This contributes directly to the UN Sustainable Development Goals (SDGs) in environmental protection, industrial innovation, and public health.